(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2014)
One hundred asterosomid specimens from 24 sections of several flysch facies of the Northern (Tuscan-Romagna-Umbrian) Apennines have been analysed to study their radial backfill using taphonomic characteristics. These characteristics include the stratinomic position in the bed, the shape and morphology of concave or convex tunnels, the type of subhorizontal crossing, the disposition and shape of wrinkles and cracks, and newly recognized fan-shaped, micro-debris flow deposits in the sides of tunnels induced by the radial backfilling compression causing shock in mud. Many types of preservation have been found in Halopoa ichnospecies while other preservational aspects (Asterosoma and Lennea in primis, while the Fucusopsis preservation and aspect has been included in ichnogenus Halopoa). This comparative taphonomic study enhances, for the first time in the turbidites of Apennines, the role of radial backfill as a type of deposit-feeding in deep-sea firmgrounds and softgrounds, produced by soft-bodied organisms (probably worms).